THE EFFECTIVENESS OF USING SERIES OF PICTURESIN TEACHING NARRATIVE WRITING(AN EXPERIMENTAL STUDY IN THE SECOND GRADE OF SMAN 1 CILEGON STUDENTS) - Dini Maulida, - (2008)
The focus of this research was to investigate the effectiveness of using series of pictures in teaching narrative writing at the second grade of senior high school students. It was also to find out the advantages and the disadvantages of using this kind of media. A quasi experimental design was used to conduct the research. The samples of this study were an experimental group and control group. The experimental group was given the treatment, while the control group was not given any treatment. Data collection was taken from pretest and posttest, interview, and questionnaire. The independent t-test fromula were used to analyze the data of tests. Meanwhile, the data from questionnaire and interview were analyzed to examine the advantages and the disadavantages of using series of pictures. The research findings showed that series of pictures were effective to teach narrative writing. In addition, the data result from questionnaire and interview showed that series of pictures had advantages and disadvantages both for students and teacher.